(untitled) (Educação e Pesquisa, 2007)
This is a theoretical article of a philosophical-educational nature, whose aim is to analyze the knowledge-power device of didactics, and to propose the epistemological basis for the construction of a Didactics of the Work of Art. Based on the post-structuralist perspective, notably on Michel Foucault's work, the text realizes an archaeology of the didactic discourses of the Bible, of Comenius' Didactica Magna, of Rousseau's Emile, and of Dewey's Democracy and Education, observing that these discourses share, despite their specificities and different objects, the same broad paradigm according to which the scientific knowledges of communication are structured. Still from a post-structuralist outlook, now focusing on the ideas of Gilles Deleuze and Felix Guattari, the article expounds the epistemological basis for the construction of new forms of thinking didactics or the education-communication relation. Just as Deleuze and Guattari affirmed the existence of a pedagogy of the Concept, one can propose a Didactics of the Work of Art. Such didactics, which understands the didactic relation as agency, and the communication as redundancy and observation, can help us to understand the moments at which the process of teaching and learning occurs between the world of noise and that of the construction of meaning, the world of creation.